Pengembangan Media Pembelajaran Berbasis Game Edukasi Digital pada Materi Sistem Reproduksi untuk Meningkatkan Kemampuan HOTS pada Siswa SMA/MA - Jelita Purnama Sari; Rasyidah (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to develop a digital educational Game-based learning medium on the human reproductive system material to enhance students’ Higher Order Thinking Skills (HOTS). The research method employed the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were high school students studying the reproductive system. Data were collected through expert validation questionnaires, classroom observations, and tests to measure the improvement of students’ HOTS. The results showed that the developed digital educational Game has a high level of feasibility based on assessments from material and media experts. Its classroom implementation demonstrated improvements in students’ HOTS, particularly in the aspects of analysis, evaluation, and creation. In conclusion, this medium is effective as an innovative and interactive biology learning alternative that stimulates higher-order thinking skills. Keywords: Digital Educational Game, HOTS, Human Reproductive System